Comparative effectiveness and safety of 32 pharmacological interventions recommended by guidelines for coronavirus disease 2019: a systematic review and network meta-analysis combining 66 trials. Issue 16 (20th August 2021) - Wu, Shan-Shan; Zhou, Qing-Xin; Zeng, Xue-Yang; Zhang, Jing-Xue; Yang, Zhi-Rong; Yang, Qing-Qing; Zhang, Zi-Lu; Chen, Ya-Hong; Sun, Feng; Zhan, Si-Yan
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The global pandemic coronavirus disease 2019 (COVID-19) has become a major public health problem and presents an unprecedented challenge. However, no specific drugs were currently proven. This study aimed to evaluate the comparative efficacy and safety of pharmacological interventions in patients with COVID-19. Methods: Medline, Embase, the Cochrane Library, and clinicaltrials.gov were searched for randomized controlled trials (RCTs) in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/SARS-CoV. Random-effects network meta-analysis within the Bayesian framework was performed, followed by the Grading of Recommendations Assessment, Development, and Evaluation system assessing the quality of evidence. The primary outcome of interest includes mortality, cure, viral negative conversion, and overall adverse events (OAEs). Odds ratio (OR) with 95% confidence interval (CI) was calculated as the measure of effect size. Results: Sixty-six RCTs with 19, 095 patients were included, involving standard of care (SOC), eight different antiviral agents, six different antibiotics, high and low dose chloroquine (CQ_HD, CQ_LD), traditional Chinese medicine (TCM), corticosteroids (COR), and other treatments. Compared with SOC, a significant reduction of mortality was observed for TCM (OR = 0.34, 95% CI: 0.20–0.56, moderate quality) and COR (OR = 0.84, 95% CI: 0.75–0.96, low quality) with improved cure rate (OR = 2.16, 95% CI: 1.60–2.91, low quality for TCM; OR = 1.17, 95% CI: 1.05–1.30, low quality for COR). However, an increased risk of mortality was found for CQ_HD vs . SOC (OR = 3.20, 95% CI: 1.18–8.73, low quality). TCM was associated with decreased risk of OAE (OR = 0.52, 95% CI: 0.38–0.70, very low quality) but CQ_HD (OR = 2.51, 95% CI: 1.20–5.24) and interferons (IFN) (OR = 2.69, 95% CI: 1.02–7.08) vs . SOC with very low quality were associated with an increased risk. Conclusions: COR and TCM may reduce mortality and increase cure rate with no increased risk of OAEs compared with standard care. CQ_HD might increase the risk of mortality. CQ, IFN, and other antiviral agents could increase the risk of OAEs. The current evidence is generally uncertain with low-quality and further high-quality trials are needed.